Integrasi Nilai-Nilai Maqashid Shariah dalam Inovasi Keuangan Digital Bank Syariah: Kajian Literatur Terstruktur - Setiawan, Jaka; Munjazim, Munjazim; Ulya, Desti; Amalia, Lutfi; Azizah R, Alifah; Faizah N, Izza; Sulasih, Sulasih (Jurnal Ekonomi, Bisnis dan Manajemen, 2025)
This study aims to analyze the integration of maqasid al-shariah within digital financial innovation in Islamic banking and to identify patterns in previous research through a Systematic Literature Review (SLR). The SLR method was employed to search, select, and synthesize relevant studies published between 2020 and 2025 using predefined inclusion and exclusion criteria, followed by thematic analysis. The findings were organized into five core themes: security and wealth protection, digital literacy, regulatory and shariah compliance, adoption of digital technologies, and the orientation toward justice and social benefit. The results indicate that the integration of maqasid al-shariah in digital innovation remains partial and has not been developed into an operational framework for the design or evaluation of digital banking services. Prior studies emphasize the importance of data security and regulatory readiness but have not formulated measurable maqasid-based indicators. This synthesis highlights the need for a more applicable maqasid-driven digital framework to strengthen governance, risk mitigation, and the strategic direction of digital innovation in Islamic banking.